Exploring Governance Satisfaction Among Rural Barangay Leaders in the City of Calamba, Philippines - Aguilar III, Exequiel (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the quality of governance among rural barangay chairmen and its impact on constituents’ satisfaction in the City of Calamba. It aimed to evaluate how well principles of good governance—such as accountability, transparency, responsiveness, fairness, legitimacy, effectiveness, and participation—are practiced. This study aimed to address these gaps by examining the qualities of leadership and governance practices at the barangay level. By identifying the strengths and weaknesses of barangay leadership in promoting good governance, this study contributed to the broader discussion on local governance and its significance in national development. A causal research design was employed, using a self-administered questionnaire to gather data from 17 barangay chairmen and 340 constituents, totaling 357 respondents. Findings indicated that good governance was rated as "Extremely Manifested" across all measured dimensions, with high satisfaction levels among constituents regarding policy implementation, fund disbursement, and barangay operations. However, even though the findings indicate that transparency and responsiveness are manifested, these principles do not significantly influence constituents' satisfaction with good governance in rural barangays of Calamba City. On the other hand, a significant positive relationship was found between the level of good governance practices and constituents’ satisfaction. Governance in rural barangays of Calamba City shows a strong commitment to budget accountability, with a need to strengthen adherence to treasury regulations for comprehensive governance excellence. These findings highlight the effectiveness of current governance practices and suggest areas for continued focus to overcome governance challenges and promote sustainable development. The results revealed that there was a significant relationship between the levels of manifestation and constituents’ satisfaction.